Decadal Review of Human Resource Analytics Research - Chong, Luther Yuong Qai; Lim, Thien Sang; Nipo, Debbra Toria (Journal of Technology Management and Business, 2024)
Human Resource analytics is a trending tool that helps companies achieve competitive advantage, and it is constantly evolving to meet the dynamic needs of modern businesses. The constant influx of new research in human resource analytics floods scholars with vast amounts of information in qualitative and conceptual research, making researchers difficult to navigate and identify key contributions. This study evaluates publication trends over the past decade and aims to reveal evolving research patterns. Subsequently, the focus shifts to identify the most influential sources in HR analytics research. Finally, pinpoint emerging themes within HR analytics publications aims to offer valuable insights into current trends and guide future research in this field. This study analyzed 262 articles sourced from the Scopus database using VOSviewer. Using scientific mapping of literature and performance analysis, the discussion encompasses publication trend, geographical distribution of research, identification of influential publications, and emerging trends. A consistent upward trend in HR analytics publications since 2019, with notable publications in different regions, reflect its growing global significance. Interestingly, ethical considerations persist as a central theme, while research focus shifts from general HR topics to specific areas and technology-related terms. The analysis also highlights the evolution of HR analytics into a cross-disciplinary field, incorporating computer science terms, indicating transformative potential for traditional HR practices. The findings provide direction for researchers and organizations, ensuring they remain abreast of the latest developments in the field.